UPAYA-UPAYA PENINGKATAN PEMAHAMAN DAN KESADARAN PENCIPTA KARYA SENI TRADISIONAL TERHADAP HAK CIPTANYA - Yolanda, Nina (Faculty of Law, University of Palembang, 2019)
The research objective is to describe and analyze efforts to increase the understanding and awareness of the creators of traditional art works on their copyright. Writing method uses normative juridical method. Research results: efforts to increase understanding and awareness of creators of their copyright are carried out through efforts to promote intellectual property rights such as counseling, discussions, seminars, workshops, symposiums, intellectual property education and training and institutionally established a Copyright Council. In the end, it was suggested that arrangements regarding copyright law protection, especially the copyright of traditional artworks, need to be accompanied by consistent law enforcement and efforts to increase understanding and awareness of creators of their copyright needs to be intensified both in terms of quality and quantity